A Case Study on Research Postgraduate Students’ Understanding of Academic Integrity at a Hong Kong University - Lau, Peter (Frontiers in Education, 2021)
This case study aims to understand how research postgraduate (RPg) students at a Hong Kong university perceive academic integrity before and after participating in the Trail of Integrity and Ethics on the general issues of academic misconduct (TIE-General learning trail), which makes use of Augmented Reality (AR) technology and mobile application to help students acquire abstract concepts (Wong et al., 2018). A total of 33 RPg students, who had completed the mandatory courses on research ethics and teaching skills, successfully completed the TIE-General learning trail. The participants were required to demonstrate their levels of understanding of academic integrity and ethics before and after going through the learning trail. Results of the thematic analysis on the participants’ responses indicated that the RPg students were generally able to show some understanding of the six fundamental values of academic integrity defined by the International Center for Academic Integrity (ICAI), namely honesty, trust, fairness, respect, responsibility, and courage. Among these six values, the findings suggested that honesty and respect might be the most familiar values to the participants. However, the other four values seemed to be less familiar to them. On top of the above six values, empathy and mindfulness were considered as two other important attributes of academic integrity from the participants’ perspectives. This article analyses the possible impacts of empathy and mindfulness on the academic integrity development of university students.